Flux Filling Rate Effect on Weld Bead Deposition of Recycled Titanium Chip Tubular Wire - Moreno-Uribe, Andrés M.; Fagundes, José Gedael [UNESP]; Criscuolo, Izabel L.; Hassel, Thomas; Bracarense, A. Q. (Springer Nature, 2025)
TiC-reinforced composite coatings were fabricated in situ on carbon steel plates using flux-cored arc welding with tubular wire. The flux was composed of titanium powder recycled from chips generated during the machining process. The microstructure of the welded deposits was formed using various metal strip thicknesses to fabricate the wires, resulting in different flux fill values. During welding, titanium chips melted and reacted with carbon to form TiC. The complex in situ-formed phases were beneficial for improving the coating properties. Results indicated that the microhardness of the composite coatings using a greater quantity of flux was enhanced to over four times that of the substrate. More TiC resulted in better hardness values with increased amounts of flux. However, using thick metal strips reduces the flux supply, thereby diminishing the formation of a wear-resistant microstructure.
Keywords: Experimental tubular wire; Flux filling rate; Hardfacing; Recycled Titanium chip